Redesign Interior in Yulia 1 Homestay, Sanur, Denpasar Selatan, Bali Application of Scandinavian Concepts - Prasetya, I Gede Eka; Wiryawan, I Wayan (Journal of A Sustainable Global South; Vol 2 No 1 (2018): February 2018DO - 10.24843/jsgs.2018.v02.i01.p04, 2018)
Tourism in Bali is an important economic sector for the people of Bali. Tourism is synonymous with an lodging. In every place, especially tourist destinations, there must be many lodging facilities. Sanur as one of the tourist destinations cer-tainly has many choices of lodging places such as homestays, competition between homestays in attracting interested local and foreign guests is getting tighter. The bedroom and bathroom are the most important part of a homestay. In de-signing space in the bedroom and bathroom of Yulia 1 Homestay Sanur uses the Scandinavian Concept in the hope of giving a different identity than other homestays without reducing comfort. The Scandinavian concept has a neutral color and simple character in the selection of furniture. Index Terms — interior design, homestay, bedroom, bathroom, scandinavian.